Mixed Methods in Tactical Analysis Through Polar Coordinates and Function Estimation: The Transition Play in ACB Basketball - Pastrana-Brincones, José Luis; Troyano-Gallegos, Belén; Morillo-Baro, Juan Pablo; López de Vinuesa-Piote, Raimundo; Vázquez-Diz, Juan Antonio; Reigal-Garrido, Rafael E.; Hernández-Mendo, Antonio; Morales-Sánchez, Verónica (Frontiers in Sports and Active Living, 2021)
Nowadays, getting advantageous offensive situations in high-level basketball is being increasingly harder, so taking advantage of any situation in the game since the team has the ball is essential to be competitive. Therefore, the goal to achieve in this study is to evaluate using a mixed method strategy the behaviors happening in the application of the technical-tactical means performed in the transition play of professional basketball in Spain. An ad hoc observation tool made of 11 criteria and 83 exhaustive and mutually exclusive categories (E/ME) has been designed and validated by means of Data Quality and Generalizability analyses. Indexes got show a high reliability and validity allowing the proposed actions to be recorded (correlation coefficients are above 0.95 and Generalizability coefficients, above 0.90 in all cases). A total number of 128 situations corresponding to 8 games of Unicaja de Málaga in the Endesa League in the 18/19 season were observed with the Hoisan software. The analysis of the relationships among behaviors was performed using the Polar Coordinates technique where the one-on-one initiation, outside the zone, has been used as focal behavior. The estimation of the functions representing the vectors has also been performed to model the best fit that estimates, starting from a focal category, the relationship among this focal behavior and the rest of the mating behaviors for possible future observations. The results show significant relationships between the selected focal behavior and the mating behaviors, showing indications of behaviors allowing tactical interpretation of the game and the definition of intervention programs to improve the performance in the team.